Influence of Dynamic Ozone Dry Deposition on Ozone Pollution. Issue 8 (22nd April 2020) - Clifton, O. E.; Paulot, F.; Fiore, A. M.; Horowitz, L. W.; Correa, G.; Baublitz, C. B.; Fares, S.; Goded, I.; Goldstein, A. H.; Gruening, C.; Hogg, A. J.; Loubet, B.; et al.
Abstract: Identifying the contributions of chemistry and transport to observed ozone pollution using regional‐to‐global models relies on accurate representation of ozone dry deposition. We use a recently developed configuration of the NOAA GFDL chemistry‐climate model—in which the atmosphere and land are coupled through dry deposition—to investigate the influence of ozone dry deposition on ozone pollution over northern midlatitudes. In our model, deposition pathways are tied to dynamic terrestrial processes, such as photosynthesis and water cycling through the canopy and soil. Small increases in winter deposition due to more process‐based representation of snow and deposition to surfaces reduce hemispheric‐scale ozone throughout the lower troposphere by 5–12 ppb, improving agreement with observations relative to a simulation with the standard configuration for ozone dry deposition. Declining snow cover by the end of the 21st‐century tempers the previously identified influence of rising methane on winter ozone. Dynamic dry deposition changes summer surface ozone by −4 to +7 ppb. While previous studies emphasize the importance of uptake by plant stomata, new diagnostic tracking of depositional pathways reveals a widespread impact of nonstomatal deposition on ozone pollution. Daily variability in both stomatal and nonstomatal deposition contribute to daily variability in ozone pollution. Twenty‐first century changes in summer deposition result from a balance among changes in individual pathways, reflecting differing responses to both high carbon dioxide (through plant physiology versus biomass accumulation) and water availability. Our findings highlight a need for constraints on the processes driving ozone dry deposition to test representation in regional‐to‐global models. Key Points: Remote and local ozone depositional sinks shape regional winter ozone pollution Dynamic ozone dry deposition changes summer surface ozone over northern midlatitude regions by −4 to +7 ppb Variability and 21st-century changes in both stomatal and nonstomatal deposition influence summer surface ozone distributions